2017
DOI: 10.1021/acs.jmedchem.6b01447
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of Pyrazolopyridine Derivatives and Their Potential as an Adjunct Therapy with Miltefosine

Abstract: A series of pyrazolo(dihydro)pyridines was synthesized and evaluated for antileishmanial efficacy against experimental visceral leishmaniasis (VL). Among all compounds, 6d and 6j exhibited better activity than miltefosine against intracellular amastigotes. Compound 6j (50 mg/kg/day) was further studied against Leishmania donovani/BALB/c mice via the intraperitoneal route for 5 days and displayed >91 and >93% clearance of splenic and liver parasitic burden, respectively. Combination treatment of 6j with a subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…9 These compounds, from the concentration of 25 μg/mL, did not differ statistically in the antileishmanial effect when compared to the reference drug. The presence of the pyridine ring, although not a significant influence in Bex activity has been shown to be an essential pharmacophoric moiety in other classes of compounds with leishmanicidal potential, such as chalcones, 24 pyrazoles, 25 and dyarylimidazoles. 26 In addition, the Bexs employed in this study had similar effects on the promastigotes of L. (V.) braziliensis and L. (L.) infantum, suggesting that they may be used in chemotherapy of both, CL and VL.…”
Section: Resultsmentioning
confidence: 99%
“…9 These compounds, from the concentration of 25 μg/mL, did not differ statistically in the antileishmanial effect when compared to the reference drug. The presence of the pyridine ring, although not a significant influence in Bex activity has been shown to be an essential pharmacophoric moiety in other classes of compounds with leishmanicidal potential, such as chalcones, 24 pyrazoles, 25 and dyarylimidazoles. 26 In addition, the Bexs employed in this study had similar effects on the promastigotes of L. (V.) braziliensis and L. (L.) infantum, suggesting that they may be used in chemotherapy of both, CL and VL.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows some compounds that have been reported to be active against Leishmania parasite: A pentamidine‐aplysinopsin hybrid was effective against L. donovani promastigotes with an EC 50 of 2 μ m and a selectivity index of 53 . A combination of low doses of miltefosine and pyrazolopyridine derivatives were reported to decrease liver and spleen parasite burden by more than 89 % in rodent model, with EC 50 values of 7 μ m and 4 μ m against promastigotes and amastigotes, respectively . Further immunological and molecular studies showed that their lead compound exhibited a dual effect by acting as an immunostimulant and by directly killing the parasites .…”
Section: Resultsmentioning
confidence: 99%
“…[30] Further immunological and molecular studies showed that their lead compounde xhibited ad ual effectb ya cting as an immunostimulant and by directly killing the parasites. [30] Di-indolylmethane has been reported to be an inhibitor of L. donovani topoisomerase Iw ith an EC 50 of 1.2 mm, [31] while paullone derivatives have shown EC 50 values < 1 mm on axenic amastigotes, and high inhibition of L. donovani in infectedm acrophages at 5 mm. [11c] Pyrazolopyridine derivatives had EC 50 values < 1 mm on L. amazonensis promastigotes [32] and indazole N-oxide derivative induced high parasite lysis against L. amazonensis, L. infantum and L. braziliensis promastigotes at 100 mgmL À1 ,p ossibly by inducing damages into parasitec ells due to the nucleophilic properties of the compounds.…”
Section: Published Compounds With Indole/indazole-like Scaffoldsmentioning
confidence: 99%
“…This method is advantageous relative to mainstream synthetic frameworks in easy set-up, cost-effectiveness and high yield. Recently, several MCRs have been used effectively to build nitrogen-heterocyclic compounds especially the indole substructure that possesses distinct pharmacological and biological activities [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%